-4(3-6d)=2d-2

Simple and best practice solution for -4(3-6d)=2d-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3-6d)=2d-2 equation:


Simplifying
-4(3 + -6d) = 2d + -2
(3 * -4 + -6d * -4) = 2d + -2
(-12 + 24d) = 2d + -2

Reorder the terms:
-12 + 24d = -2 + 2d

Solving
-12 + 24d = -2 + 2d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-2d' to each side of the equation.
-12 + 24d + -2d = -2 + 2d + -2d

Combine like terms: 24d + -2d = 22d
-12 + 22d = -2 + 2d + -2d

Combine like terms: 2d + -2d = 0
-12 + 22d = -2 + 0
-12 + 22d = -2

Add '12' to each side of the equation.
-12 + 12 + 22d = -2 + 12

Combine like terms: -12 + 12 = 0
0 + 22d = -2 + 12
22d = -2 + 12

Combine like terms: -2 + 12 = 10
22d = 10

Divide each side by '22'.
d = 0.4545454545

Simplifying
d = 0.4545454545

See similar equations:

| 2x+80=5x+44 | | y-17/19=-13/19 | | 30=0.3x | | 6+2x=102 | | (N+0)+(n+1)=-389 | | w^2=77 | | 8.5+j=17.6 | | 7x=6x+72 | | 5/3x+1/3x=211/3+7/3x | | 392/2 | | 1/12+3/8y=5/12 | | 5x+26(x-2)=103 | | 5(5x+22)=5 | | 4x-45=x^2 | | derp= | | KLN=9x-7 | | -(3a+4a-6)+2(9a+3)+3(-8a)= | | 2(11m-10)+6m=-6(-6m+2)-8 | | 13m-5=4m | | 784/2 | | 4(2x-5y)=-13 | | 4.3(g-7)=2(10+g) | | N+(n+1)=-389 | | 0.15y+0.08(y+7000)=1480 | | 7f-2(f+8)=29 | | r^2+8r-29=0 | | 10+6X-3= | | 6.5+j=12 | | x+3=7x-35 | | c(2c+3)+c-3(7+4c)= | | 2c-15=c+4 | | 4x+x+4x+x+5=180 |

Equations solver categories